An investigation into the worldview of a selected group of Norwegian Army Cadets from a complexity and leadership perspective - Ronn, Harald (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.